1997
DOI: 10.1103/physrevb.55.12210
|View full text |Cite
|
Sign up to set email alerts
|

Diffusive transport properties in monovalent and divalent metal-ion halide melts:A computer simulation study

Abstract: Self-and cross-velocity correlation functions and related transport coefficients of molten salts are studied by molecular-dynamics simulation. Six representative systems are considered, i.e., NaCl and KCl alkali halides, CuCl and CuBr noble-metal halides, and SrCl 2 and ZnCl 2 divalent metal-ion halides. Computer simulation results are compared with experimental self-diffusion coefficients and electrical conductivities. Special attention is paid to dynamic cross correlations and their dependence on the Coulomb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
47
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 43 publications
9
47
1
Order By: Relevance
“…In order to study the structural and transport properties in molten salts, experimental investigations and molecular dynamics simulations have also been carried out from mid 70s of the last century [7][8][9][10][11]. Following these studies, we have been recently engaged in the study of transport properties in molten salts [12][13][14][15].…”
Section: Introductionmentioning
confidence: 98%
“…In order to study the structural and transport properties in molten salts, experimental investigations and molecular dynamics simulations have also been carried out from mid 70s of the last century [7][8][9][10][11]. Following these studies, we have been recently engaged in the study of transport properties in molten salts [12][13][14][15].…”
Section: Introductionmentioning
confidence: 98%
“…Higher values for cation self-diffusion coefficients as compared with those for anions were obtained also by Koishi et al [24], Mitev et al [29] and Belashchenko and Ostrovskii [30]. Unfortunately, electrical conductivities calculated using simulated self-diffusion coefficients given in these works and Nernst -Einstein equation are much higher [17,23,24] or much lower [30] than experimental data [3, this work]. It should be noted that self-diffusion coefficients of molten CuCl obtained as results of experiments [54] give also an unusually large ratio D + / D À , which seems to be a significant feature of those liquid halides whose solid phase immediately below the melting point is a fast-ion conducting crystal.…”
Section: Liquid Cubrmentioning
confidence: 69%
“…Nevertheless, values estimated theoretically can be found in a few papers [17,23,24,29,30]. To our knowledge, self-diffusion coefficients of the cation D + and of the anion D À for molten CuBr at a single temperature 800 K have for the first time been evaluated by Trullas et al and Trullas and Padro [17,23] using molecular dynamics simulation. They found a significant difference between D + and D À , as opposed to e.g.…”
Section: Liquid Cubrmentioning
confidence: 97%
See 1 more Smart Citation
“…3. Ciccotti [34] and Trullas [35][36][37][38] have studied the single ion dynamics of molten alkali halides and reported that ionic mass and size significantly affect the single ion dynamics, for molten alkali chlorides, the smaller the ion is, the larger diffusivity it has. However, for the molten alkali halide mixtures, the ionic dynamics is more complicated.…”
Section: Self-diffusion Coefficientsmentioning
confidence: 98%